2013
DOI: 10.1371/journal.pone.0066412
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Latent Tuberculosis Infection among Health Care Workers in China: A Cross-Sectional Study

Abstract: BackgroundHealth care workers (HCWs) are at risk of latent tuberculosis infection (LTBI). In China, tuberculosis (TB) is a major public health problem, but the prevalence of LTBI in HCWs especially in the hospital for pulmonary diseases has not been assessed enough. The aim of this study was to determine the prevalence and putative risk factors of LTBI among HCWs in a chest hospital and a TB research institute in China.Methodology/Principal FindingsA cross-sectional study was conducted among HCWs in China in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
41
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 25 publications
(33 reference statements)
10
41
2
1
Order By: Relevance
“…The risk of Diabetes was lower when compared to other risk group like prisoners, illicit drug users, homeless people and health care workers, HIV /AIDS, patients on TNF alpha inhibitors, hemodialysis, nevertheless these are data from the low prevalent TB countries. Various studies have shown that employment categories at highest risk include healthcare workers and gold miners [9,25,26] ; participants in our study worked in diverse settings but none were in the known high-risk categories. Our findings and those from previous studies suggest a potential need for periodic LTBI screening coupled with preventive treatment programs at workplaces but the cost-effectiveness of such an intervention should be evaluated.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The risk of Diabetes was lower when compared to other risk group like prisoners, illicit drug users, homeless people and health care workers, HIV /AIDS, patients on TNF alpha inhibitors, hemodialysis, nevertheless these are data from the low prevalent TB countries. Various studies have shown that employment categories at highest risk include healthcare workers and gold miners [9,25,26] ; participants in our study worked in diverse settings but none were in the known high-risk categories. Our findings and those from previous studies suggest a potential need for periodic LTBI screening coupled with preventive treatment programs at workplaces but the cost-effectiveness of such an intervention should be evaluated.…”
Section: Discussionmentioning
confidence: 95%
“…This finding was in agreement with studies done in Uganda, Thailand, and China which have reported more transmission at home due to household contact exposure [15][16][17][18][19] . However, other studies have shown that more transmission happens outside home especially in work places like healthcare settings due to nosocomial transmission [9,20,21,22] . Others demonstrate higher transmission among students in the healthcare settings, prisoners and gold miners [9,23,24,25] which are higher risk populations.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the USA, unemployment was associated with EPTB [12,16]. This is the case too in China [27] and Japan too [28]. Indeed, having a job provides income, improves standard of living, prevent from promiscuity and thus protects against tuberculosis.…”
Section: Discussionmentioning
confidence: 99%